CHARACTERIZATION OF NEWBORN LOW AND VERY LOW WEIGHT NASAL CPAP IN A NEONATAL INTENSIVE CARE UNIT WEST PARANÁ (Fiep Bulletin - online, 2012)
In Brazil the incidence of premature newborns lies at around 11%, and the population of the neonatal ICU is close to 50%. Newborns (RN's) are especially suffering from lung diseases and is a major cause of morbidity and mortality. Among the many current strategies for the treatment of neonates, continuous positive airway with nasal prongs (nasal CPAP) has been used for a ventilation mode to be effective and noninvasive, and low cost. The study on the prevalence of nasal CPAP in newborn's low and very low birth weight neonatal ICU HUOP covered a period of 12 months, 23 RN's were selected that met the criteria for inclusion and exclusion. Most infants underwent CPAP occurred after a period of invasive mechanical ventilation. We analyzed the clinical and laboratory records at the time of initiation and discontinuation of therapy. Most infants received application of the technique of CPAP from 36 to 48 hours. It was concluded that the percentage of RN's who have been successful (35%) and those considered as failure (25%) therapy, progressing to invasive mechanical ventilation.
Keywords: Continuous Positive Airway; ventilation; prematurity.